A Replication stress biomarker is associated with response to gemcitabine versus combined gemcitabine and ATR inhibitor therapy in ovarian cancer - Panagiotis A. Konstantinopoulos (Nature Portfolio, 2021)
A randomized phase 2 study recently showed that the addition of ATR inhibitor berzosertib to gemcitabine improved PFS compared to gemcitabine alone in patients with ovarian cancer. In this preplanned exploratory study, the authors demonstrate that a genomic biomarker of replication-stress is associated with outcome to gemcitabine alone and may predict which patients benefit from addition of the ATR inhibitor berzosertib.